Analysis of Students' Social Skills in Futsal Learning at High School Level - Alfhadil Akbar; Yunyun Yudiana; Carsiwan (Universitas Negeri Semarang, 2026)
Social skils are an important aspect that must be developed in students,as they support interaction,cooperation,and adaption in the school environment.However,not all students demonstrate optimal social skills,especially in activities that require teamwork and communication.Therefore,interactive learning approaches are needed,one of which is physical education through futsal. This study aims to analyze the tendency of students social skills in futsal learning at Senior High School 4 Tasikmalaya.it uses a quantitative approach with a descriptive trend analysis method without treatment.the subject were 94 students from classes X,XI,and XII.Data were collected using a validated and reliable questionnaire covering cooperation,communication,sporsmanship,responsibility,discipline,and empathy.Data analysis used descriptive statistics with percentage techniques. The result show that student social skills are generally in the very good category,with percentages of 97% for clas X,94% for clas XI,and 95% for class XII.These findings indicate that futsal learning plays are role in supporting the development of students social skills and can be used as an effective learning medium in schools.